Vocational Psychology with Criminal Justice Populations: Why Not?. (October 2013) - Varghese, Femina P.; Fitzgerald, Erica L.; Chronister, Krista M.; Cummings, Devon L.; Forrest, Linda
In this rejoinder, the authors respond to the three reactions by Brown, Lent, and Knoll; McWhirter; and Morgan. We begin by discussing illegal work and desistance and how vocational psychology may inform these areas. We then acknowledge the challenges in working with criminal justice populations and describe how counseling psychologists may overcome these challenges. We conclude by encouraging counseling psychologists to persist through challenges and pursue excellence in applying vocational theories and best practices to promote the positive career development of offenders.